Boosting bean-based products: scaling SMEs in Malawi and Zambia - Munthali, Justice; Katungi, Enid; Nkhata, Wilson; Rubyogo, Jean Claude (2024)
Market and consumer-oriented product development and optimization interventions encompassing rapid market assessments, sensory evaluation and consumer acceptability, food safety and nutrition quality assessments, processing and production factors assessments, and willingness to pay studies were implemented through private-public partnerships in Malawi and Zambia. Seven small-scale processors improved their product production and marketing — four processors adopted improved and optimized product formulations; one newcomer (processor) entered the bean-based food market; and two improved their processing procedures, production capacity, and marketing prowess.